The Effect of Discipline and Work Motivation on Employee Performance, BTPN Gorontalo - Ismet Sulila (AIBPM Publisher, 2019)
Performance is an important aspect of the organization. Performance can be influenced by various factors, including discipline and work motivation. Therefore the purposes of this study are 1) to find out to what extent the influence of Discipline on Employee Performance; 2) to know to what extent the influence of the Work Motivation on Employee Performance; 3) to figure out to what extent the influence of simultaneous discipline and work motivation on Employee Performance. This quantitative method employed multistage sampling that was done in stages. It was based on the scope of employees in BTPN Gorontalo. The analysis tool used was a mathematical model of Multiple Linear Regression with SPSS 16.0. Moreover, all BTPN Gorontalo employees were taken as the population in this study. The results of the t-test of variable of discipline significantly influence employee performance seen from tcount (4,388) ¬>ttable(1,729); while the variable of work motivation has a significant effect on employee performance behavior seen from tcount (2,379) > ttable (1,729). Based on the calculated value of 13,532 with a p-value (sig. Value) of 0,000. This value is much lower than 0.05, which means it has simultaneous effect. According to the calculation of the determination coefficients, it is obtained R Square value of 0.501. This value means 50.1% of the variability regarding Employee Performance can be explained by the independent variables in the model (Discipline and Work Motivation), while the remaining 49.9% is influenced by other variables.